Constraints and Prospects of Faith-Based Refugee Protection in Kakuma Refugee Camp, Kenya - Oduor, Kevin; Abuya, Edwin; Ouma, Martin (African Human Mobility Review, 2025)
This article investigates three distinct elements of faith-based organizations (FBOs) in refugee protection: their challenges, the appropriate solutions, and the opportunities available for FBOs to leverage. Knowledge about the three elements is critical in helping FBOs function effectively and efficiently. Unlike the relevant existing literature, the article focuses on issues that relate specifically to FBOs, not those that extend to almost all refugee-protection actors. The focus is on FBOs because they are usually the first responders to conflict-related crises, maintain their presence throughout all stages of a conflict, and are identified by the Global Compact on Refugees as key players in protecting refugees. The research collected data from the Kakuma refugee camp in Kenya using focus group discussions (FGDs), key informant interviews, and general observations of the refugee environment. It analyzed the data using qualitative content analysis. The results indicate that specific challenges exist for FBOs in refugee protection. Nevertheless, these challenges are not beyond resolution; they merely necessitate a shift in strategy or perspective. Despite the various challenges outlined, the contributions made by FBOs remain substantial and are valued highly by refugees, host communities, and other humanitarian entities. Furthermore, there is considerable potential for enhancing the operational effectiveness of FBOs.